Curvas dinamicas de crecimiento en altura dominante para Terminalia amazonia (Gmel.) Excell en Costa Rica - Montero Mata, M.; Kanninen, M.; Santos Posadas, H.M. de los (2006)
A set of dominant height equations based on the Chapman-Richards and Hossfeld models were fitted to data from even-aged plantations of Terminalia amazonia in Costa Rica. The equations were classified as dynamic or algebraic difference equations, defined as expected mean value structures and fitted under a multilevel mixed effect model criterion. The best statistical fit is produced by the polymorphic Chapman-Richards structure, but the model overestimates height development at the intermediate age range (12 to 20 years). The multi-asymptotic polymorphism equation derived from Hossfeld shows fit conditions similar to the polymorphic Chapman-Richards and better represents the growth pattern since the equation design is a compromise between single asymptote polymorphism and anamorphic growth curves.